The religious dimension in the vocabulary of the Algerian revolution (1954-1962) - tahri, fatima; djouiba, abdelkamel (Journal of Social Sciences and Humanities, 2023)
The form of the Islamic religion is one of the main pillars that contributed to the start of the Algerian revolution, and the fact is that the role of Islam in the revolution cannot be limited to one article, so we’ll focus in this research paper that we have, on one part of this topic, which is an attempt to know the extent of the